Conceptual Analysis of the Importance of Leadership Style in Educational Organizational Behavior - Anissaa Alhaqqoh Darwis; Agus Saputra; Anita Triana Apriyanti; Wulan Noviyanti Asyarah; Zunus Matori; Yudo Dwiyono (International Journal of Economics Accounting and Management, 2024)
Leadership style is a major factor that greatly influences the dynamics and performance of an organization. This article will explore in depth the importance of leadership style in organizational behavior. Through a conceptual analysis supported by various literature reviews, this article will explain how leadership style impacts job satisfaction, productivity, innovation, and organizational culture. In addition, this paper will also highlight the impact of leadership style on overall organizational success. The leadership style applied by a leader can affect various aspects of an organization, including work culture, employee motivation, and overall organizational effectiveness and performance. This article aims to explore the importance of leadership styles in organizational behavior through a literature review and conceptual analysis. The main focus is to identify various leadership styles, analyze their influence on organizational behavior, and provide recommendations for effective integration between leadership and organizational behavior